Inhibition of EETosis with an anti-citrullinated histone antibody: a novel therapeutic approach for eosinophilic inflammatory disorders - Zwiers, Eline; Montizaan, Daphne; Kip, Annemarie; Waaijenberg, Kelsy; Fichtinger, Paul S.; Mathur, Sameer K.; Fujioka, Yuki; Ueki, Shigeharu; van Es, Helmuth; Chirivi, Renato G. S.; Meldrum, Eric; van der Linden, Maarten (Frontiers in Immunology, 2025)
Eosinophils are a subset of granulocytes that protect the host against fungal and parasitic infection through secretion of their granular contents. In response to specific stimuli, eosinophils also undergo a type of lytic cell death, referred to as eosinophil extracellular trap (EET)-associated cell death (EETosis), where histone citrullination facilitates chromatin decondensation, cell rupture and release of pro-inflammatory, decondensed chromatin into the extracellular environment as EETs. In this study, we show the abundant presence of eosinophils and citrullinated histones in nasal polyp tissue of patients with eosinophilic chronic rhinosinusitis (ECRS). Using live imaging microscopy on purified human eosinophils, we demonstrate that physiologically relevant stimuli induce release of citrullinated EETs and the marker of eosinophil activation galectin-10. While the kinetics of release of EETs and galectin-10 are similar, inhibitors of citrullination block EETosis in a dose dependent manner but fail to inhibit galectin-10 release. The importance of citrullination is further exemplified with CIT-013, a monoclonal antibody specific for citrullinated histones H2A and H4. CIT-013 potently inhibits release of EETs (half-maximal inhibitory concentration of 2.5 nM) without inhibiting other eosinophil functions such as degranulation, adhesion, superoxide production and induction of chemokine expression. Together, this study provides new insights into the requirement of protein arginine deiminase 4 (PAD4) for EETosis, differentiates requirements of EETosis from galectin-10 release, and identifies a novel therapeutic approach for EETosis inhibition by targeting citrullinated histones in eosinophil-driven diseases such as ECRS.